2013
DOI: 10.1074/jbc.m112.434340
|View full text |Cite
|
Sign up to set email alerts
|

The Overexpression of Hypomethylated miR-663 Induces Chemotherapy Resistance in Human Breast Cancer Cells by Targeting Heparin Sulfate Proteoglycan 2 (HSPG2)

Abstract: Background: miR-663 is related to chemosensitivity in human breast cancer cells. Results: Overexpression of miR-663 was associated with chemoresistance and accompanied by down-regulation of HSPG2. Conclusion: Overexpression of hypomethylated miR-663 induces chemoresistance in breast cancer cells by down-regulating HSPG2. Significance: Learning how miR-663 regulates chemoresistance may provide a potential target for the miRNA-based approach of breast cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 24 publications
3
72
0
1
Order By: Relevance
“…miRNAs bind primarily to the 3'-untranslated region (3'UTR) of their target messenger RNAs (mRNAs) to reduce their stability and decrease the expression of target mRNAs at the post-transcriptional level (13), which play important roles in various biological processes including cell growth, proliferation, differentiation and death (14)(15)(16)(17)(18)(19). Concerning chemotherapy in various types of cancers such as breast cancer, lung adenocarcinoma, glioblastoma, and ovarian cancer, recent studies have shown that miRNAs also act in important roles (20)(21)(22)(23)(24). In ESCC, altered expression of miR-1290, miR-655, miR-375 and others, has been observed (25)(26)(27), suggesting that miRNA deregulation plays an important role in ESCC development.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs bind primarily to the 3'-untranslated region (3'UTR) of their target messenger RNAs (mRNAs) to reduce their stability and decrease the expression of target mRNAs at the post-transcriptional level (13), which play important roles in various biological processes including cell growth, proliferation, differentiation and death (14)(15)(16)(17)(18)(19). Concerning chemotherapy in various types of cancers such as breast cancer, lung adenocarcinoma, glioblastoma, and ovarian cancer, recent studies have shown that miRNAs also act in important roles (20)(21)(22)(23)(24). In ESCC, altered expression of miR-1290, miR-655, miR-375 and others, has been observed (25)(26)(27), suggesting that miRNA deregulation plays an important role in ESCC development.…”
Section: Introductionmentioning
confidence: 99%
“…Microarray and qRT-PCR results all showed that upon exposure to PT, miR663b decreased dramatically in EC cells. We have previously described the oncogenic function of miR-663 in breast cancer [19] . Many studies reached the same conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue in situ hybridization for miRNA detection In our previous paper, we used ISH to demonstrate that miR-663 is overexpressed in breast cancer [19] . Here, we evaluated mIR-663 levels in 51 cases of EC using tissue paraffin sections.…”
Section: Western Blot Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs have been revealed to be associated with cell chemosensitivity or chemotherapy resistance in a variety of cancer cell types, including ovarian and breast cancer cells (6)(7)(8). However, there is limited available data on the potential role of miRNAs in the chemotherapy resistance of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%